Phone directory information system PDIS / Tan Yin Shuen - Tan, Yin Shuen (2002)
This project can be define as a system, which attempts to communicate with the outside, and inside flow of information stored and provide the function. common for all applications. This information system allows users to perform their intended task such a information searching, sending email or message and on the other hand, lets the authorized administrators to update the data stored. The rationale behind this development into eliminate all the difficulties faced when trying to search through the conventional channel, i.e. flipping through paper documents or files.A combination of waterfall mode; and prototyping model approach was selected for the development process because it supports for the rapid application development and reduces the risk. Software engineering principles based on this methodology were applied through the development phases. Theses include system analysis system design, system implementation, system testing and evaluation phases. The main development tools for this project is Visual Basic 6.0 programming language and the back bend database used is Microsoft Access 2000 with Windows 98 as the operating system.